Increasing The Learning Achievement Of Indonesian History, in Indonesia Nation Efforts Facing The Nation Disintegration through The Team Quiz Plus Method Outcomes - Roessajanto, Gigieh (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
The purpose of this study was to determine the improvement of student learning achievement in learning Indonesian History in the material